EFEKTIVITAS KEGIATAN KELOMPOK KERJA GURU (KKG) - Dewa Agung Putri Widiasih (Pascasarjana Universitas Hindu Indonesia, 2017)
The act No. 14 of 2005, article 1, paragraph 1 states that the teachers are professional educators with the primary task of educating, teaching, guiding, directing, training, assessing and evaluating the students on the early childhood education, formal education, primary education, and middle educa- tion. The teachers are required to carry out the process of learning which includes exploration, elabo- ration and confirmation to change the educational paradigm, which is from the paradigm of teaching to the paradigm learning. The obstacle for the teachers is that because they have abandoned the strat- egy of teacher-centered learning (teacher center oriented) strategies in order to work on the student- centered learning orientation.